(untitled) (Research, Society and Development, 2022)
Non-surgical rhinoplasty has become an interesting option for most patients because it is a quick procedure that will produce results comparable to rhinoplasty surgery. The procedure consists of remodeling the nasal structure by means of injectable fillers or the use of a definitive thread, which will pull the dermis tissue. These techniques end up improving the anatomy of the nose, creating a harmonious and natural face. Rhinomodelation has been shown to be safe and effective, with low incidences of postoperative complications. It is a procedure that in most cases does not involve the use of anesthesia and there are no long periods of postoperative recovery. Thus, the present study aimed to report a clinical case of a patient who was seen at a referral clinic, with nasal morphological or dynamic defects, where she had a prominent nasal dorsum and a slightly drooping nose tip. The patient underwent a rhinomodeling procedure in the treatment of modifying the appearance of the nose with the use of Hyaluronic Acid filler. The result of the procedure and the patient’s postoperative period were highly satisfactory, with no complications whatsoever.